ActionScript 3.0 programming : overview, getting started, and examples of new concepts - Sanders, William B., 1944- (O'Reilly shortcuts., 2007)
ActionScript 3.0 Programming: Overview, Getting Started, and Examples of New Concepts is a 76-page document designed to introduce those familiar with general programming principles to ActionScript 3.0. ActionScript 3.0 compiles and runs much faster than preceding versions, and the reasons have much to do with the structural changes Adobe has added: You truly do need to use ActionScript differently than you have previously, if you're already ActionScript programmer. If you're new to ActionScript, but are looking at it from a Java or C++ or C# perspective, you may be intrigued at how different.